2019
DOI: 10.1002/ccr3.2111
|View full text |Cite
|
Sign up to set email alerts
|

Multidisciplinary clinical approach by sharing oral examination information to treat a diabetes patient with dysgeusia

Abstract: Key Clinical Message Taste alteration is one of the complications of severe diabetes. It is important in diabetes treatment to assess taste alteration and perform dietary counseling, therapeutic exercise, and oral care. In this case, multidisciplinary clinical approach by medical staff was successful for a severely diabetic patient with dysgeusia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…Xerostomia is a common symptom of COVID-19 infection approved in a study by Tsuchiya et al (24). Additionally, xerostomia and dysgeusia are mentioned as oral manifestations of diabetic patients (25,26). The observations of diabetic patients in this study showed that xerostomia and dysgeusia were exacerbated in diabetic patients and even after discharge from the hospital.…”
Section: Discussionmentioning
confidence: 99%
“…Xerostomia is a common symptom of COVID-19 infection approved in a study by Tsuchiya et al (24). Additionally, xerostomia and dysgeusia are mentioned as oral manifestations of diabetic patients (25,26). The observations of diabetic patients in this study showed that xerostomia and dysgeusia were exacerbated in diabetic patients and even after discharge from the hospital.…”
Section: Discussionmentioning
confidence: 99%